Implementation of MBKM Program on Islamic Education Learning in Improving Critical Thinking at Darul Hikmah Bangkalan High School - Tri Wahyudi Ramdhan; Mufaizin Mufaizin; Moh. Holil Baitaputra; Bustomi Arisandi (International Journal of Islamic Educational Research, 2024)
In the industrial era 4.0 and advanced technology like today, teachers are faced with very tough challenges, especially PAI teachers, whose learning requires a clearer and more concrete picture. In this era, sources of information or learning are very easy to obtain, learning models and media are very innovative and formal education is required to produce quality students. This research is about how the independent learning program and its implementation in PAI learning for class X at SMA Darul Hikmah Burneh Bangkalan , aims to find out about the independent learning program and its implementation in PAI learning in increasing the critical thinking of class X students at SMA Darul Hikmah Burneh Bangkalan . This study uses a descriptive qualitative approach with field study methods and data collection techniques through observation, interviews and documentation. The results of the research on the implementation of the independent learning program in PAI class X at SMA Darul Hikmah Burneh Bangkalan , learning includes 3 aspects (intracurricular, co-curricular and extracurricular). With learning media using teaching modules, power points and computers.